2019
DOI: 10.1177/1536012118821034
|View full text |Cite
|
Sign up to set email alerts
|

Altered Forebrain Functional Connectivity and Neurotransmission in a Kinase-InactiveMetMouse Model of Autism

Abstract: MET, the gene encoding the tyrosine kinase receptor for hepatocyte growth factor, is a susceptibility gene for autism spectrum disorder (ASD). Genetically altered mice with a kinase-inactive Met offer a potential model for understanding neural circuit organization changes in autism. Here, we focus on the somatosensory thalamocortical circuitry because distinct somatosensory sensitivity phenotypes accompany ASD, and this system plays a major role in sensorimotor and social behaviors in mice. We employed resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…These structures, present in the spontaneous activity of the brain, show a certain level of conservation across different cell types, ages, and even species (humans and mice) 24 , 43 . Although state-dependent FC has been identified in various contexts, the synchronization of global neural activities extends beyond the simple superposition of synchronized or desynchronized states 8 14 . FC encompasses a more intricate picture as a highly multidimensional continuum of synchronizations, including a time lag (or traveling waves, which may be initially interpreted as a desynchronized state) and differences between cells 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These structures, present in the spontaneous activity of the brain, show a certain level of conservation across different cell types, ages, and even species (humans and mice) 24 , 43 . Although state-dependent FC has been identified in various contexts, the synchronization of global neural activities extends beyond the simple superposition of synchronized or desynchronized states 8 14 . FC encompasses a more intricate picture as a highly multidimensional continuum of synchronizations, including a time lag (or traveling waves, which may be initially interpreted as a desynchronized state) and differences between cells 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Source data are provided as a Source Data file. simple superposition of synchronized or desynchronized states [8][9][10][11][12][13][14] . FC encompasses a more intricate picture as a highly multidimensional continuum of synchronizations, including a time lag (or traveling waves, which may be initially interpreted as a desynchronized state) and differences between cells 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engrailed-2 (En2) knockout adult mice, which show a lower expression of FMR1 and anatomical defects common to FMR1 knockout, significantly reduce synchronization in the somatosensory-auditory/associative cortices and the dorsal thalamus ( Chelini et al, 2019 ). Functional connectivity between the somatosensory cortex and the thalamus is significantly reduced in conditionally mutant adult Met-Emx1 mice expressing a kinase-dead Met restricted to the cerebral cortex and the hippocampal structures ( Tang et al, 2019 ). Adult BTBR T + Itpr3tf/J (BTBR) mice, originally bred for studies on insulin resistance, diabetes-induced nephropathy, and phenylketonuria, show a reduction in long-range functional connectivity involving retrosplenial areas and lateral cortical regions ( Sforazzini et al, 2016 ).…”
Section: Autism Spectrum Disorder Mouse Modelmentioning
confidence: 99%
“…It has been previously reported that in thalamocortical slices prepared from Met cKO mice, the E/I ratio is biased toward excitation due to decreased GABA A receptor-mediated inhibition (Lo, Erzurumlu, & Powell, 2016), an effect that may be due to insulin fails to increase GABA A receptor-mediated response in the barrel cortex of Met cKO mice. Another recent study employed resting-state functional magnetic resonance imaging and in vivo high-resolution proton MR spectroscopy to examine neuronal connectivity (Tang et al, 2019). The study focused on somatosensory thalamocortical circuitry because somatosensory disturbances are frequently reported co-morbid conditions with ASD, and may be responsible for altered sensorimotor gating and for processing the saliency of social behaviors.…”
Section: Me T S I G Naling S Hape S the De Velopmental Synap Tic Anmentioning
confidence: 99%